2021
DOI: 10.1186/s12887-021-03065-5
|View full text |Cite
|
Sign up to set email alerts
|

Intussusception in preterm neonates: A systematic review of a rare condition

Abstract: Background While necrotizing enterocolitis (NEC) is a prevalent condition in preterm neonates admitted to neonatal intensive care unit (NICU), intussusception is exceedingly uncommon and often overlooked. This is due to the fact that they share many clinical characteristics. The initial misdiagnosis of intussusception in preterm neonates (IPN) especially has led to a delay in their management, which increases the risk of developing compromised bowel. Additionally, it is difficult to reach a dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Due to the similar symptomatology of NEC and intussusception and the high prevalence of NEC in this age group, AUS is recommended for differential diagnosis to avoid the delayed treatment of intussusception in premature infants. A systematic review including 43 studies with a total of 52 cases of intussusception reported between 1963 and 2020 has revealed that the most common location was the small bowel, detecting colo-colic intussusception in two cases only (Kotb et al, 2021 ). A sigmoid-rectal intussusception (without perforation) was found in a preterm during monitoring the progression of stage IIIA NEC, which disappeared after a few hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the similar symptomatology of NEC and intussusception and the high prevalence of NEC in this age group, AUS is recommended for differential diagnosis to avoid the delayed treatment of intussusception in premature infants. A systematic review including 43 studies with a total of 52 cases of intussusception reported between 1963 and 2020 has revealed that the most common location was the small bowel, detecting colo-colic intussusception in two cases only (Kotb et al, 2021 ). A sigmoid-rectal intussusception (without perforation) was found in a preterm during monitoring the progression of stage IIIA NEC, which disappeared after a few hours.…”
Section: Discussionmentioning
confidence: 99%
“…Key AUS features of NEC were observed carefully (Tam et al, 2002 ; Faingold et al, 2005 ; Epelman et al, 2007 ; Silva et al, 2007 ; Muchantef et al, 2013 ; Patel et al, 2015 ; Allin et al, 2017 ; Erinumberger, 2017 ; Chen et al, 2018 ; Faingold, 2018 ; Markel and Underwood, 2018 ; Ben Fadel et al, 2019 ; van Druten et al, 2019 ; Miller et al, 2020 ; Tracy et al, 2020 ; Alexander et al, 2021 ; Chan et al, 2021 ; Gao et al, 2021 ; Kotb et al, 2021 ; Cuna et al, 2022 ; Hwang et al, 2022 ). These features included (1) bowel wall thickness: normal between 1 and 2–2.7 mm; (2) decreased intestinal peristalsis: intestinal peristalsis <10 times/min.…”
Section: Methodsmentioning
confidence: 99%